Uganda : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criteria, and Request for a Policy Support Instrument; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses Uganda's Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), Request for Waiver of Performance Criteria, and Request for a Policy Support Instrument (PSI). Performance relative to the sixth and final PRGF review was satisfactory. The authorities request waivers for two performance criteria that were not observed by small margins. Corrective measures will be undertaken during 2006. The authorities have also requested a PSI to begin immediately after the current PRGF arrangement expires.